2015
DOI: 10.2519/jospt.2015.5033
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the QuickDASH in Patients With Shoulder-Related Disorders Undergoing Surgery

Abstract: Study Design Validity study. Objective To determine the validity of the shortened version of the Disabilities of the Arm, Shoulder and Hand questionnaire (QuickDASH) in comparison to the full DASH in patients undergoing total shoulder arthroplasty (TSA) and rotator cuff repair (RCR). Background The QuickDASH is a shorter version of the DASH that may reduce respondent burden while retaining similar measurement properties. Methods One hundred thirty-two patients undergoing TSA or RCR were assessed at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 55 publications
1
43
2
Order By: Relevance
“…3 In a previous study, 4 we found that the QuickDASH scores were 2.8 points higher than the full DASH scores in patients with neck pain, whereas in the present study 3 of patients with shoulder disorders, this was only about 1 point. The more recently introduced QuickDASH is rapidly gaining acceptance and, like its parent version, is thought to represent a single conceptual domain (upper extremity-related disability).…”
Section: Responsecontrasting
confidence: 59%
“…3 In a previous study, 4 we found that the QuickDASH scores were 2.8 points higher than the full DASH scores in patients with neck pain, whereas in the present study 3 of patients with shoulder disorders, this was only about 1 point. The more recently introduced QuickDASH is rapidly gaining acceptance and, like its parent version, is thought to represent a single conceptual domain (upper extremity-related disability).…”
Section: Responsecontrasting
confidence: 59%
“…3.Yes5The correlation between change scores of DASH and AROM abduction is moderately and negatively correlated ( r  = − .50–0.69). This hypothesis is based on findings in previous studies [46, 58]. Yes6The correlation between change scores of DASH and AROM of abduction is higher than the correlation between change scores of DASH and other AROM movements.…”
Section: Methodsmentioning
confidence: 89%
“…Shoulder pain is one of the most commonly reported musculoskeletal problems that result in the restriction of work and/or social activities [1][2][3]. Rotator cuff disorders (RCDs) are the most common causes of shoulder pain, as chronic tendon degeneration of the cuff results in a loss of tendon integrity that ranges from partial to massive tears [3]. RCDs are highly prevalent in males, and more frequent in working individuals over the age of 60 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Rotator cuff disorders (RCDs) are the most common causes of shoulder pain, as chronic tendon degeneration of the cuff results in a loss of tendon integrity that ranges from partial to massive tears [3]. RCDs are highly prevalent in males, and more frequent in working individuals over the age of 60 [2,3]. Overall, untreated RCDs eventually lead to the loss of quality of life (QoL) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation